Fostering Critical and Creative Thinking Skills Using Differentiated Student Worksheet (LKPD) in Primary Science Education - Septiana Anggraini; Banu Setyo Adi (Didaktika: Jurnal Kependidikan, 2025)
The research study investigates the impact of differentiated student worksheets (LKPD) on the development of critical and creative thinking skills among fifth-grade students in elementary science learning (IPAS). The research employed a quasi-experimental design involving students from District IV, Klaten Regency SDN 1 Tambongwetan, Kalikotes District, Klaten Regency. Data were collected through pretest and posttest assessments using validated test instruments, and analyzed using both descriptive statistics and inferential analysis. The findings reveal a significant improvement in students’ critical thinking skills, with an average increase of 24.2 points, and in creative thinking skills, with an average increase of 26.03 points, following the implementation of differentiated LKPD. Furthermore, hypothesis testing using a multivariate test showed a significance value of 0.0001 (< 0.05), confirming that differentiated LKPD had a statistically significant positive effect on both critical and creative thinking abilities in simultanly. These results highlight the potential of differentiated learning materials to foster higher-order thinking skills in primary school students, supporting a more personalized and effective science education experience.